Physically Crosslinked Chondroitin Sulfate (CS)-Metal Ion (M: Fe(III), Gd(III), Zn(II), and Cu(II)) Particles for Versatile Applications and Their Biosafety - Selin S. Suner; Mehtap Sahiner; Evrim Umut; Ramesh S. Ayyala; Nurettin Sahiner (MDPI AG, 2023)
Chondroitin sulfate (CS), a well-known glycosaminoglycan, was physically crosslinked with Fe(III), Gd(III), Zn(II), and Cu(II) ions to obtain CS-Fe(III), CS-Gd(III), CS-Zn(II), and CS-Cu(II) polymeric particles for multipurpose biological applications. The CS-metal ion-containing particles in the micrometer to a few hundred nanometer size range are injectable materials for intravenous administration. The CS-metal ion-containing particles are safe biomaterials for biological applications because of their perfect blood compatibility and no significant cytotoxicity on L929 fibroblast cells up to a 10 mg/mL concentration. Furthermore, CS-Zn(II) and CS-Cu(II) particles show excellent antibacterial susceptibility, with 2.5-5.0 mg/mL minimum inhibition concentration (MIC) values against Escherichia coli and Staphylococcus aureus. Moreover, the in vitro contrast enhancement abilities of aqueous CS-metal ion particle suspensions in magnetic resonance imaging (MRI) were determined by obtaining T1- and T2-weighted MR images using a 0.5 Tesla MRI scanner and by calculating the water proton relaxivities. Therefore, these CS-Fe(III), CS-Gd(III), CS-Zn(II), and CS-Cu(II) particles have significant potential as antibacterial additive materials and MRI contrast enhancement agents with less toxicity.